Six new species of Calicnemia Strand, 1926 and one new species of Coeliccia Kirby, 1890 (Odonata: Zygoptera: Platycnemididae) from northeastern India - Sawant, Dattaprasad; Joshi, Shantanu; Pawar, Ujwala; Khan, Fahim; Nawge, Viraj; Kunte, Krushnamegh (Zootaxa, 2026)
We erect six new species of the genus Calicnemia Strand, 1926, namely, Ca. ardena sp. nov., Ca. arunachala sp. nov., Ca. flavovittata sp. nov., Ca. mimumkoa sp. nov., Ca. naga sp. nov. and Ca. rubromacula sp. nov.; and one new species of Coeliccia Kirby, 1890, Co. magna sp. nov., from northeastern India. The new Calicnemia spp. are distinguished based on the structure of the genital ligula, colouration patterns of the thorax and abdomen, and the shape of caudal appendages. Based on the morphology of the genital ligula, we propose a third species group within Calicnemia, in addition to the two previously recognised species groups. This new species group accommodates Ca. ardena sp. nov. and Ca. rubromacula sp. nov., which possess short, bifurcated genital filaments that do not align with the diagnostic characteristics of the existing species groups. Additionally, Ca. erythromelas (Selys, 1891) previously reported from India is shown to be misidentified, and the Indian material is identified as Ca. naga sp. nov. Updated identification keys for all known Calicnemia males are provided, along with detailed illustrations of diagnostic features. Coeliccia magna sp. nov., erected from Arunachal Pradesh, is distinguished from congeners by its larger body size, complete blue antehumeral stripes, and distinct male and female morphological features. We further provide lateral thoracic illustrations of Coeliccia spp.